Understanding degraded speech leads to perceptual gating of a brainstem reflex in human listeners - Hernandez Perez, Heivet; Mikiel-Hunter, Jason; McAlpine, David; Dhar, Sumitrajit; Boothalingam, Sriram; Monaghan, Jessica J.M.; McMahon, Catherine M. (Dryad, 2020)
The ability to navigate “cocktail-party” situations by focussing on sounds
of interest over irrelevant, background sounds is often considered in
terms of cortical mechanisms. However, subcortical circuits such as the
pathway underlying the medial olivocochlear (MOC) reflex modulate the
activity of the inner ear itself, supporting the extraction of salient
features from auditory scene prior to any cortical processing. To
understand the contribution of auditory subcortical nuclei and the cochlea
in complex listening tasks, we made physiological recordings along the
auditory pathway while listeners engaged in detecting non(sense)-words in
lists of words. Both naturally spoken and intrinsically noisy, vocoded
speech—filtering that mimics processing by a cochlear
implant—significantly activated the MOC reflex, but this was not the case
for speech in background noise, which more engaged midbrain and cortical
resources. A model of the initial stages of auditory processing reproduced
specific effects of each form of speech degradation, providing a rationale
for goal-directed gating of the MOC reflex based on enhancing the
representation of the energy envelope of the acoustic waveform. Our data
reveals the co-existence of two strategies in the auditory system that may
facilitate speech understanding in situations where the signal is either
intrinsically degraded or masked by extrinsic acoustic energy. Whereas
intrinsically degraded streams recruit the MOC reflex to improve
representation of speech cues peripherally, extrinsically masked streams
rely more on higher auditory centres to de-noise signals.
Dataset includes all sound and sentence wav-files used to generate
auditory nerve spikes.  Model of the auditory periphery and
auditory brainstem (MAP_BS) is the work of Meddis group and is
available here but can also be originally found (alongside more
information about previous versions of the model)
at http://essexpsychology.webmate.me/HearingLab/modelling.html.  Please refer to https://www.researchgate.net/publication/307583615_MAP-BSa_Matlab_Auditory_Processing_software_platform_for_studying_Auditory_BrainStem_activity for further information about MAP_BS and its origins. Two analysis files are included to perform Shuffled Auto-/Cross- Correlograms of either Individual Words (list of words used in the article are found in 'Balanced_NS_and_S_lists.mat') or Mava Corpus sentences (https://app.alveo.edu.au/catalog/mava).
Please read README.docx for an overview of source data
in this dataset. There is also reading material to understand
workings of MAP_BS Auditory nerve model (included in
MAP_BSpublic_forDryad.zip). Please unzip
Additional_PlosBio_files_for_MAP_BS.zip for custom mfiles and
instructions on how to run simulations/analysis for individual words.